Design and Testing of a Piezoelectric Ultrasonic Transducer - Liu, Zhenyu (International Journal of Mechanical and Electrical Engineering, 2025)
Carbon fiber composite materials have been widely used in the aerospace field. However, traditional milling processes struggle to meet their machining requirements. To achieve high-quality milling of carbon fiber composites, a compact sandwich transducer suitable for ultrasonic machining and capable of generating large amplitudes was proposed. Firstly, the basic dimensions of the stepped horn were designed based on wave propagation theory. Subsequently, a transducer model was established using Abaqus software, and modal analysis along with harmonic response analysis were conducted to verify the theoretical design. Finally, an experimental platform was built to perform impedance analysis and amplitude testing on the fabricated transducer. The results show that its maximum longitudinal output amplitude is 7.384μm. Its performance meets the requirements of most ultrasonic milling applications, thereby validating the correctness of the design methodology.